"Exit" vs. "Voice": Global Sourcing, Multinational Production, and the China Trade Lobby. (June 2021) - Zeng, Ka
Abstract: This paper examines the influence of three different forms of global economic engagement on the lobbying behavior of US businesses with regard to trade relations with China: (a) input sourcing; (b) downstream export; and (c) vertical foreign direct investment. It will be hypothesized that firms involved in all three forms of global economic activities should have incentives to lobby over China-related trade issues in order to maintain unimpeded access to sources of supply or markets and to ensure the smooth operation of the entire supply chain. Going further, drawing on the exit-voice framework developed by Albert Hirschman (1972 ), it will be argued that compared to firms in those industries mainly involved in input sourcing from China, American multinational corporations that have verticalized their production should have even stronger incentives to engage in lobbying activities and "voice" their policy preferences due to their greater "sunk costs" and hence the higher cost of "exit." Statistical analysis of the China trade-related lobbying activities of US firms between 2006 and 2016 lends substantial support to these conjectures.